The effect of Learning Facility, Attention of Parents, and Learning Motivation on Student Achievement at State Senior High School 2 Kampar District - Anggraini, Fetri; Nas, Syakdanur; Sumarno, Sumarno (Program Pascasarjana, Universitas Riau, 2018)
This study aims to determine the effect of learning facilities, parental attention, and motivation to learn student achievement. This type of research is quantitative research. This research was conducted in SMA Negeri 2 Kampar. The population of this study were students of SMA Negeri 2 Kampar, while the sample of 106 students. Data were collected with questionnaires and documentation instruments. Data analysis technique used is path analysis. The results of this study indicate that learning facilities have a significant effect on students' learning motivation. Attention parents significantly influence the motivation of student learning. Learning facilities have a significant effect on student achievement. Attention parents significantly influence on student achievement. Learning motivation has a significant effect on student achievement. Learning facilities significantly influence the attention of parents. Learning facilities have a significant effect on learning achievement through student learning motivation. Attention parents significantly influence on learning achievement through student learning motivation